Formulation and Characterization of Propranolol Nanoparticles for Transmucosal Nasal Drug Delivery. Issue 1 (January 2015) - Nag, Payal; Rajput, Rashi; Dhaliwal, Sonam; Kumar, Sachin; Prajapat, Deepak; Singh, Manisha; Bhattacharya, Bhaskar
Summary Essential hypertension remains a major modifiable risk factor for cardiovascular diseases (CVD) despite important advances in our understanding of its pathophysiology and the availability of effective treatment strategies. Available evidences and researches favour the utility of non selective beta‐adrenergic receptor blocking agents. Propranolol belongs to this class and is indicated for treatment of hypertension. Owing to its low bioavailability (26%) and extensive hepatic metabolism, reduction in absorption and elaborative side effects in patients, it is not assumed as an ideal drug candidate for oral drug delivery. Hence, it would be beneficial if it is given through an alternate route, bypassing gastro‐ intestinal degradation, for faster therapeutic effect, enhanced bioavailability and less dosage. To address these issues, transmucosal nasal drug delivery promises as an interesting alternative. The objective of this study was to develop propranolol nanoparticles for transmucosal nasal drug delivery through ionic gelation method. The Particle size analysis, zeta potential, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) studies confirmed a nanometric size range of nanoparticles below 200 nm, with nearly spherical morphology. Moreover, rheological parameters indicated a good stability of the optimised nanoparticle formulation. In‐vitro drug release and cytotoxicity results showed sustained release of the drug till 24 hours along with less cytotoxicity.